Socio-Cultural Exposition of Islamic Teachings: As modus operandi for Establishing a Welfare Society (Al-Qamar, 2023)
There are a large number of religions on the globe. Everyone claims the welfare of human beings. We can understand their claims by examining their teachings either by pointing out their differences or by discovering their similarities or common characteristics. The comparison will expose that any religions has focused any aspect of humanity but leaving the other corner. Some emphasis on beliefs, the other stresses on the performances; the one focuses on ethics, the other one follows the natural objectifications and anthropomorphism. Some rejects the existence of any supernatural beings the other has made it central point. Consequently, on these claims they want to establish a human society. But the dark side is that, all these have no focus on such a welfare society where every person belonging to any contrary religion or ideology can live with peace and without any fear of cruelties. So, there is a need for such a theory which without any pressure can guarantee to anyone to live with peace, liberty and fraternity in a society.Islam places a strong emphasis on social justice, charity, and the well-being of society, making it inherently connected to the concept of a welfare society. The principles of social justice and economic equality are embedded in various aspects of Islamic teachings and practices. Thus, present article provides the insights that Islamic teachings are the guiding principle, if they are followed for the establishing of a welfare society.  There would be peace for every member of that welfare society despite one’s belonging to any sect or any ideology or any frame of politics.
Keywords: Culture; Epistemology; Fundamental Rights; Humanism; Islamic Preaching; Welfare-Society; Well-Being